A multilevel analysis of the effect of Malawi's Social Cash Transfer Pilot Scheme on school-age children's health. Issue 4 (9th May 2013) - Luseno, Winnie K; Singh, Kavita; Handa, Sudhanshu; Suchindran, Chirayath
Abstract: Objective The primary goal was to examine whether Malawi Social Cash Transfer Pilot Scheme, initially implemented in a rural district in central Malawi, improved health outcomes for children aged 6–17. Secondary goals were to examine the effects of individual child- (orphan status and gender) and household-level factors (number of working-age adults and sick adults) on health outcomes. Another secondary goal was to examine whether orphan status modified the cash transfer effect on health outcomes. Methods This multilevel study used panel data collected in 2007–08 from a randomized controlled evaluation study of phase one of the programme. The analyses included 1197 children aged 6–17 in 486 households. The four outcomes of interest were: illness in the past month, illness that stopped normal activities in the past month, missing school due to illness or injury in the past month and health care use for worst illness in the past year. Findings Approximately two-thirds of children in cash transfer eligible households were orphans. Compared with children in non-beneficiary households, those in beneficiary households had a 37% lower odds of child illness ( P < 0.05), 42% lower odds of illness that stopped normal activities ( P < 0.01) and substantially higher odds of utilizing health services for a serious illness (odds ratio = 10.98; P < 0.01). An increase in the household number of working-age adults was associated with 34% lower odds of child illness ( P < 0.01). An increase in the household number of sick adults increased the odds of child illness by 97% ( P < 0.01) and serious illness by 49% ( P < 0.01). No statistically significant differences were observed by orphan status and child's gender. Consistent differential programme effects by orphan status were not observed. Conclusion Unconditional cash transfer programmes to poor households have the potential to improve health outcomes for all vulnerable children aged 6–17.